2023
DOI: 10.1039/d2nr07256d
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid-loaded polymeric nanoparticles prepared from nano-emulsion templates facilitate internalisation across the blood–brain barrier in model membranes

Abstract: A hydroxycinnamic acid derivative, namely ferulic acid (FA) has been successfully encapsulated in polymeric nanoparticles (NPs) based on poly(lactic-co-glycolic acid) (PLGA). FA-loaded polymeric NPs were prepared from O/W nano-emulsion templates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 120 publications
1
7
0
Order By: Relevance
“…The study showed an EE of 90% at a concentration of 0.1 mg/mL and 79% at a concentration of 0.3 mg/mL of FA. In this study, it is possible to observe a lower EE and an increase in particle size at the highest tested concentration of FA, results that are in line with the findings of our own study …”
Section: Results and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The study showed an EE of 90% at a concentration of 0.1 mg/mL and 79% at a concentration of 0.3 mg/mL of FA. In this study, it is possible to observe a lower EE and an increase in particle size at the highest tested concentration of FA, results that are in line with the findings of our own study …”
Section: Results and Discussionsupporting
confidence: 93%
“…In this study, it is possible to observe a lower EE and an increase in particle size at the highest tested concentration of FA, results that are in line with the findings of our own study. 22 In addition, the pH obtained for the nanoemulsions without FA was close to 6, and that for NE-FA HO and NE-FA MCT ,it was close to 4, probably due to the FA acidic character. It was also observed that the higher the FA concentration incorporated, greater is the tendency to the acidic character of the nanoemulsion.…”
Section: Nanoemulsion Characterizationmentioning
confidence: 80%
See 3 more Smart Citations